Marketing international luxury brands in China - Lebreton, Tiphaine (2006)
Most international luxury brands have been enticed by the potential of long term profits in an increasingly wealthy nation of 1.3 billion consumers hungry for a taste of Western luxury and globally recognized logos. The increase of the middle class traveling abroad and taking cues from fashion magazines and TV programmes at home wants modernity and to be at the fore front. China is therefore an important growing market that promises high evolutions and profits for foreign brands. However, it is also a complex one where consumers differ in their behaviours and expectations. These differences generate difficulties for international luxury brands to understand them but also identify them and create specific target groups. Although they have at their disposition several segmentation techniques (geographic, demographic, psychographic/lifestyle), choosing one in particular that will generate insightful, efficient and effective results to help them establishing their strategies is not easy. This lack of understanding but also lack of research in the literature on this specific population of the world make brands facing difficulties in understanding the true needs and expectations of the consumers who, even if they have similarities with the Western ones, still did not reach the same level of sophistication. They are constantly changing and evolving so that brands have even more difficulties to undertake a proper follow up. Based on the information they gather, they, therefore, juggles between adaptation and globalization in their communication strategies trying to use integrated marketing communications playing with their foreign origins and sometimes breaking the established Western rules by using mass media communication mediums such as television. The use of public relations remains their main strategic tools but the concept is extended to the notion of guanxi omnipresent in the Chinese culture. Due to the lack of extensive secondary data focusing on transitional economies and especially Mainland China, this study attempts to collect in-depth information through the use of interviews from the major actors of the luxury industry based in the country who are either managing such brands, developing them and promoting them. Although such qualitative method has been undergoing critics by academics because of its supposedly lack of objectivity for example, the authors considers that this practice permits to provide additional knowledge and originality in the domain that might not have been possible to collect with another technique. She, however, acknowledges that the findings and conclusion generated might not represent a whole population and the functioning of Marketing international luxury brands in China. The research, nevertheless leads to key implications for managers of the industry if they want to successfully operate in Mainland China involving more adaptation and the use of less preconceived ideas regarding these new and complex consumers and hopefully a better understanding of the way marketing practices are handled in the country.